A Visual Semiotic Analysis of Multicultural Values in An Indonesian English Textbook for Primary School Students: A Qualitative Study - Melya Putri Astari; Bambang Widi Pratolo (Institut Agama Islam Negeri Palopo, 2025)
Most previous studies have analyzed multicultural values from various countries and school levels, yet not extensively examined the Indonesian textbooks for young learners. To fill this gap, this study conducts a visual semiotic analysis to explore the representation of multicultural values in an Indonesian English textbook for primary school students. Utilizing Barthes' visual semiotic theory, the research examines images from the textbook